Subpoena Power and Informational Lobbying - Arnaud Dellis; Mandar Oak (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2019)
This paper studies the role of subpoena power in enabling policymakers to make better informed decisions. In particular, we take into account the effect of subpoena power on the information voluntarily supplied by interest groups as well as the information obtained by the policymaker via the subpoena process. To this end, we develop a model of informational lobbying in which interest groups seek access to the policymaker in order to provide him verifiable evidence about the desirability of implementing reforms they care about. The policymaker is access-constrained, i.e., he lacks time/resources to scrutinize the evidence owned by all interest groups. The policymaker may also be agenda-constrained, i.e., he may lack time/resources to reform all issues. We find that if a policymaker is agendaconstrained, then he is better off by having subpoena power. On the other hand, if a policymaker is not agenda-constrained, he can be worse off by having subpoena power. The key insight behind these findings is that subpoena power, while it increases the policymaker's ability to acquire information from interest groups, it also alters the amount of information they voluntarily provide via lobbying, and that the net effect differs depending on whether or not the policymaker is agenda-constrained.
Keywords: 330